PEMETAAN TEMPAT PENAMPUNGAN SAMPAH (TPS) ILEGAL MENGGUNAKAN GEOGRAPHIC INFORMATION SYSTEM (GIS) DI WILAYAH KECAMATAN MATARAM KOTA MATARAM - Wahyudin Wahyudin (Fakultas Teknik, Universitas Wiraraja, 2019)
The purpose of this study is to determine the distribution of illegal waste collection points (TPS) and their volume, as well as the influence of geophysical factors, anthropogenic factors and population factors on the distribution of illegal waste disposal sites (TPS). This research is a descriptive study which is strengthened by the results of Illegal TPS mapping based on Global Positioning System (GPS) data using Geographic Information System (GIS). Analysis of the data used is descriptive analysis and is presented in the form of output in the form of maps and data tabulations. The results showed that the spread of locations from 43 Illegal TPS was almost evenly distributed in 9 sub-districts in Mataram District. Characteristics of Illegal TPS in terms of volume, distance from the river, type of land use, type of road occupied, and population density. The largest volume of Illegal TPS obtained was 36 m3, the location of Illegal TPS was less than 15 m from the river at 60.46% and was on the environmental road at 58.14%. While population density cannot be the main factor related to its influence on the number of illegal polling stations in Mataram District. Thus the existence of the Illegal TPS has the potential to pollute the environment because it is close to the river and in a residential environment.